Pulse and respiratory rate estimation using android smartphone - Maisarah Mokhtar (2019)
A rapidly growing field for the development of smartphone applications is the healthcare and wellness industry. Currently, there are a variety of healthcare and wellness applications (apps) in the market such as calories tracker, step tracker, and vital signs estimation. This paper presents the development of vital signs estimation Android smartphone application called VitaHealth. The three vital signs considered for VitaHealth are Pulse Rate (HR), Respiratory Rate (RR) and Oxygen Saturation (SpO2). VitaHealth supports two main functions, first to measure, calculate and estimate the three vital signs, and secondly, to provide communication between users (patients) and their healthcare providers (doctors). It uses Photoplethysmography (PPG) technique in which an Android smartphone equipped with a camera records the small pulsating changes in light intensity of the blood volume at the fingertip while the camera flash illuminates the skin of fingertip. The Red and Green channels of RGB signals in each image frame of the recorded video were extracted and undergoes image processing and Fast Fourier Transform (FFT) to derive the HR and RR measurement. On the other hand, the Red and Blue channels were used for deriving SpO2 measurement. Ten participants participated in the testing process whereby VitaHealth app was tested against the pulse oximeter to determine the accuracy. The results indicated that the average error rate for heart rate is 7.68% and heart rate readings from VitaHealth is higher than the pulse oximeter due to several factors such as movement artifacts of the finger. Conversely, the average error for oxygen saturation is 1.55%. Therefore, the accuracy for oxygen saturation measurement using VitaHealth is similar to the pulse oximeter.